Inhibitory effect of two Indian medicinal plants on aldose reductase of rat lens in vitro - Kumar R.; Patel D.K.; Laloo D.; Sairam K.; Hemalatha S. (My University, 2025)
Objective: To assesse the inhibitory effect of alcoholic extract of two Indian medicinal plants namely Ceasalpinia digyna Rottler and, Alangium lamarckii Thwaits on aldose reductase (AR) of rat lens. Methods: Rats lens were enucleated through posterior approach and their homogenate was prepared and centrifuged to obtain a clear supernatant for the determination of AR activity and protein content. Results: The alcoholic extract of Ceasalpinia digyna and Alangium lamarckii had a potent inhibitory effect on the lens AR enzyme. The IC 50 values of alcoholic extract of the selected plants were calculated and were (46.29±11.17) and (106.00±5.11) μg/mL, respectively. Quercetin was used as a positive control and its IC 50 value was (2.95±1.53) μg/mL. Conclusions: Thus, it is concluded that alcoholic extracts of the selected plant exhibit significant inhibitory effects on AR in the rat lens in vitro. © 2011 Hainan Medical College.